Analisis Kausalitas Pertumbuhan Kredit Perbankan, Bi-7 Day Repo Rate, Loan to Value (LtV), Giro Wajib Minimum (GWM), dan Pertumbuhan Ekonomi di Indonesia - Elva Yunita (Diponegoro Journal of Economics, 2022)
This study aims to analyze the causal relationship between bank credit growth, monetary stimulus policy, and economic growth in Indonesia. Credit growth in influencing economic growth can be supported by monetary stimulus policies that are able to loosen banking liquidity. This research was conducted using the documentation method on bank credit growth, economic growth (GDP), and monetary policy stimulus (BI-7 Day Repo Rate, LTV, and Statutory Reserves) and analyzed using the Vector Error Correction Model (VECM). The causality relationship between variables and speed of adjustment from short to long term were analyzed according to the existing stages. The results of this study indicate that the growth of bank credit and the BI-7 Day Repo Rate affect economic growth in Indonesia. The BI-7 Day Repo Rate also affected bank credit growth. Furthermore, economic growth in Indonesia affects the growth of bank credit and LTV. Meanwhile, the Statutory Reserves does not have a causal relationship with either bank credit growth or economic growth.